Peran Pejabat Pengelola Informasi dan Dokumentasi (PPID) Kabupaten Simeulue dalam Pelayanan dan Keterbukaan Informasi Publik - Dhara Aprilya; Said Fadhlain (Jurnal Indonesia Sosial Teknologi, 2022)
The need for information for the public cannot be avoided and is limited because of the limitations now that Indonesia is entering the data era as part of the principle of a democratic state that requires the general public to be a state, which is supported by Law No. information documentation (PPID) to appreciate fast, precise, and easy services, by creating and developing a system of information service providers. This type of research uses descriptive qualitative research methods. This research was conducted at the Office of Communication, Information and Passwords, Simeulue Regency. The theory used is Organizational Communication. Based on the research findings, the Information Communications Office of Simeulue Regency, as the information coordinator, reports to the Head of the Service who is also the Main PPID. PPID assistants are Regional Apparatus Organizations (OPD). Barriers to public information service organizations, such as the lack of information about cultural activities and performance, which have not been fully implemented by most public entities.